Role of matrix metalloprotease-9 in hyperoxic injury in developing lung - Chetty, Anne (American Physiological Society, 2008)
Matrix metalloprotease-9 (MMP-9) is increased in lung injury following hyperoxia exposure in neonatal mice, in association with impaired alveolar development. We studied the role of MMP-9 in the mechanism of hyperoxia-induced functional and histological changes in neonatal mouse lung. Reduced alveolarization with remodeling of ECM is a major morbidity component of oxidant injury in developing lung. MMP-9 mediates oxidant injury in developing lung causing altered lung remodeling. Five-day-old neonatal wild-type (WT) and MMP-9 (−/−) mice were exposed to hyperoxia for 8 days. The lungs were inflation fixed, and sections were examined for morphometry. The mean linear intercept and alveolar counts were evaluated. Immunohistochemistry for MMP-9 and elastin was performed. MMP-2, MMP-9, type I collagen, and tropoelastin were measured by Western blot analysis. Lung quasistatic compliance was studied in anaesthetized mice. MMP-2 and MMP-9 were significantly increased in lungs of WT mice exposed to hyperoxia compared with controls. Immunohistochemistry showed an increase in MMP-9 in mesenchyme and alveolar epithelium of hyperoxic lungs. The lungs of hyperoxia-exposed WT mice had less gas exchange surface area and were less compliant compared with room air-exposed WT and hyperoxia-exposed MMP-9 (−/−) mice. Type I collagen and tropoelastin were increased in hyperoxia-exposed WT with aberrant elastin staining. These changes were ameliorated in hyperoxia-exposed MMP-9 (−/−) mice. MMP-9 plays an important role in the structural changes consequent to oxygen-induced lung injury. Blocking MMP-9 activity may lead to novel therapeutic approaches in preventing bronchopulmonary dysplasia.